Analisis kualitas perairan berdasarkan metode indeks pencemaran di Pesisir Timur Kota Surabaya - Guntur Guntur; Adi Tiya Yanuar; Syarifah H. J. Sari; Andi Kurniawan (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2017)
Pollution has become the serious problem in aquatic ecosystems in Indonesia including east part of the coastal area of Surabaya City. One of the methods that can be used to analyze water quality in the coastal area is pollution index method. The method can provide information related to existing water quality in respect of utilization plan. The purpose of this study is to analyze the water quality in the coastal area in East part of Surabaya City based on the physical and chemical parameters, and then, analyze the data using pollution index method. The sampling points of this study are 10 areas in the coastal area in East Part of Surabaya City. The result of this study showed that the water parameters in the sampling points are described as follows: salinity (23.2 ± 7.33‰), pH (7.156 ± 0.356), dissolved oxygen (9.46 ± 3.364 mg/L), temperature (29 ± 1.4 °C), total suspended solid (91.9 ± 109.3 mg/L), fisibility (25.15 ± 8.9 cm), ammonia (1.3 ± 1.1 mg/L), nitrate (0.095 ± 0.14 mg/L) dan biological oxygen demand (3.738 ± 0.956 mg/L). This study indicated that the value of pollution index in East Part of Surabaya City coastal area is 4.6 that indicated the areas are slightly polluted.Pencemaran merupakan sebuah permasalahan bagi sebagian besar wilayah perairan di Indonesia termasuk wilayah perairan di pesisir timur kota Surabaya. Salah satu cara untuk menganalisis kualitas perairan di wilayah pesisir adalah dengan menggunakan metode Indeks Pencemaran. Metode ini dapat memberikan informasi mengenai kondisi perairan sesuai peruntukannya. Tujuan dari penelitian adalah menganalisis kondisi perairan Pesisir Timur Kota Surabaya berdasarkan parameter fisika dan kimia serta menganalisa nilai indeks pencemaran Perairan Pesisir Timur Kota Surabaya. Penelitian ini dilakukan dengan mengambil sampel di 10 titik di Perairan Pesisir Timur Kota Surabaya. Hasil dari penelitian ini menunjukkan nilai rata-rata parameter fisika dan kimia adalah sebagaimana berikut: salinitas 23,2 ± 7,33‰, derajat keasaman (pH) 7,156 ± 0,356, dissolved oxygen 9,46 ± 3,364 mg/L, suhu 29 ± 1,4 °C, total padatan tersuspensi 91,9 ± 109,3 mg/L, kecerahan 25,15 ±8,9 cm, amoniak 1,3 ± 1,1 mg/L, nitrat 0,095 ± 0,14 mg/L dan Biological Oxygen Demand 3,738 ± 0,956 mg/L. Penelitian ini menunjukkan kalau nilai indeks pencemaran di Perairan Pesisir Timur Kota Surabaya adalah 4,6 yang mengindikasikan perairan ini dalam kondisi tercemar ringan